1998
DOI: 10.1038/sj.bjp.0702099
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced acetylcholine induced relaxation in small mesenteric arteries from pregnant rats: an important role for endothelium‐derived hyperpolarizing factor (EDHF)

Abstract: 1 Small mesenteric arteries from pregnant rats demonstrated greater sensitivity (pEC 50 : P50.001) and maximum relaxation (P50.01) to acetylcholine (ACh) than those of control non-pregnant animals. 2 Maximum relaxation, but not sensitivity, to ACh remained greater (P50.01) in pregnant animals when evaluated in 25 mM KCl, which prevents relaxation dependent upon hyperpolarization. ACh induced relaxation in the presence of 25 mM KCl was completely inhibited in pregnant and non-pregnant groups by N o -nitro L-arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
91
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 33 publications
11
91
0
Order By: Relevance
“…3,6,9 Similarly in pregnant rats, vasorelaxation is suggested as being mediated primarily through a combination of NO-and EDHF-mediated pathways. 25 Results from the present study demonstrated a significant contribution of NO, EDHF, and PGI 2 to vasorelaxation (induced by either BK or ACh) in normal plasma-treated vessels. In contrast, the residual relaxation after treatment with RUPP plasma appeared to be mediated via pathways independent of NO.…”
Section: Discussionsupporting
confidence: 51%
“…3,6,9 Similarly in pregnant rats, vasorelaxation is suggested as being mediated primarily through a combination of NO-and EDHF-mediated pathways. 25 Results from the present study demonstrated a significant contribution of NO, EDHF, and PGI 2 to vasorelaxation (induced by either BK or ACh) in normal plasma-treated vessels. In contrast, the residual relaxation after treatment with RUPP plasma appeared to be mediated via pathways independent of NO.…”
Section: Discussionsupporting
confidence: 51%
“…More recently, a role for EDHF in the increased endothelium-dependent relaxation during pregnancy has been gradually recognized. Thus several studies demonstrated that EDHF-type responses to several endothelium-dependent agonists might be increased in rat (15) or human resistance arteries in normal pregnancy (26,37). Our results indeed further strengthen the importance of EDHF to endothelium-dependent dilatation.…”
Section: Relative Contribution Of No Pgi 2 and Edhf To Bk-induced mentioning
confidence: 99%
“…Results from two published reports indicated that the chronic estrogen elevations accompanying pregnancy were associated with increased release of a non-NO/non-prostanoid hyperpolarizing factor in mesenteric arteries (117) and aorta (118) when ACh was applied. On the other hand, in cerebral arteries, a seemingly opposite estrogen-related effect was observed.…”
Section: Regulation Of Endothelium-derived Hyperpolarizing Factor In mentioning
confidence: 99%